(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the analysis of unity, imagery and polysemy of the poetic word in the lyrics of Alexander Blok. It emphasizes that Blok’s lyrics are characterized by the stability of key words and images that create a link between early and late poems. These images and symbols have deep multivalence and are capable of revealing different facets of reality, interacting with each other in different contexts. The author examines how polysemous words change depending on the context, as well as their ability to bear the imprint of previous contexts, becoming auto-quotations. The article explores in detail the recurring motifs and images in Blok’s poetry, which provide its unity and multilayeredness.